COMMUNICATION STYLE AND CONFLICT MANAGEMENT AT SMK SCIENCE TECHNOLOGY AND BUSINESS DEPOK - Sri Rejeki Sulistiyowati; Aminah Swarnawati (ZILLZELL MEDIA PRIMA, 2025)
Communication and conflict management are crucial elements in educational leadership. This study aims to analyze the communication and conflict management styles of leaders at SMK Science Technology and Business Depok. A descriptive qualitative research method was employed, with data collected through in-depth interviews, observation, and documentation studies of six key informants. The findings reveal that the leader does not employ a single, dominant communication style. The identified communication styles were relinquishing and equalitarian, characterized by openness to input and delegation of authority, yet their application was conditional and restricted to an inner circle. Conversely, a withdrawal style was also prominent, demonstrated through avoidant and neglectful behavior towards responsibilities. In managing conflict, the leader primarily applied obliging (accommodating subordinates' interests) and compromising (finding a middle ground) styles. However, the frequent use of an avoiding style led to numerous unresolved conflicts and organizational dysfunction. This study concludes that leadership effectiveness is determined not only by authority but also by the ability to foster collaboration, trust, and functional conflict resolution. The practical implications of this research highlight the need for leadership coaching, structural communication reforms, and the implementation of clear conflict management protocols to improve the school's organizational health.